A false positive hair ethylglucuronide dosage in an alcohol abstinent patient after liver transplantation: a case report - Favrod-Coune, Thierry; Lidsky, Déborah; Vionnet, Julien; Magini, Giulia; Déglon, Julien; Broers, Barbara (Frontiers in Medicine, 2024)
The use of direct alcohol biomarkers (ethylglucuronide and phosphatidylethanol) has recently been implemented in a clinical setting. Due to their low alcohol detection threshold, high sensitivity, and specificity, these tools are very useful in the pre- and post-liver transplantation setting, where the history and physical signs are not always reliable. However, the interpretation of the results can sometimes be misleading and must be integrated into a global clinical evaluation and, more importantly, in the clinical context of each patient. We present here a case report illustrating a false-positive hair ethylglucuronide caused by the application of a capillary gel in an abstinent patient after liver transplantation. This reminds us that even the most accurate laboratory tests must be interpreted with caution.